Facile corrosion synthesis and sintering of disperse pure tetragonal zirconia nanoparticles. Issue 13 (October 2016) - Zhou, Hua; Pu, Sanxu; Huo, Junming; Cao, Wenbin; Wang, Bing; Li, Jiangong
Abstract: Disperse pure tetragonal zirconia ( t -ZrO2 ) nanoparticles smaller than 10 nm are essential for preparation of structural and functional zirconia materials, but syntheses of t -ZrO2 nanoparticles using inorganic zirconium salts usually result in severe agglomeration. In this paper, we report a hydrothermal corrosion approach for improving the dispersity of t -ZrO2 nanoparticles synthesized by precipitation using zirconium oxychloride without any surfactants. Disperse pure t -ZrO2 nanoparticles with average sizes of 4.5 and 6 nm and size distributions of 2–11 and 3–12 nm were obtained by calcining precipitates at 400 °C for 2 h and 500 °C for 0.5 h followed by HCl corrosion at 120 °C for 75 h, respectively. Disperse t -ZrO2 nanoparticles with an average size of 6 nm and a size distribution of 3–12 nm were pressed into green compacts at 500 MPa and sintered by two-step sintering (heating to 1150 °C without hold and decreasing to 1000 °C with a 10 h hold). The sintered bodies are dense pure monoclinic ZrO2 nanocrystalline ceramic with a relative density of 99.9% and an average grain size of 110 nm.